PENINGKATAN KOMPETENSI GURU DAERAH TERPENCIL MELALUI PELATIHAN PENGEMBANGAN KONTEN E-LEARNING - Suryanti, Sri; Sutaji, Deni; ., Muyasaroh; Arifani, Yudhi; Zamzamy, Muhammad (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
This Community Service activity was backgrounded by three things namely 1) obtained SPADA Grant for the development and impelementation of online learning in 2018; 2) the results of evaluation of devotion activities in 2018 and 2019 namely 80% of teachers understand mobile learning based on Augmented Reality; 3) the fact that there is a gap in the quality of education that occurs in remote areas with urban areas, so it is necessary to increase the competence of teachers in terms of learning innovation through the development of e-learning content for teachers in remote areas of Bawean Island located 80 miles or 135 km north of Java island. The geographical location and transport conditions connecting Bawean island with Gresik are the main obstacles for teachers on Bawean island to keep up with the development of science and technology.This Community Service Program Â was implemented through the stage of Strengthening the concept of e-learning followed by needs analysis workshop, e-learning system design workshop, e-learning content development workshop, Upload development results to LMS system, then implementation with assistance from the service team and continued implementation independently by the school. The result of this activity were 1) increased teacher understanding of e-learning and examples of its implementation; 2) produced an e-learning design consisting of the design of the materials of each meeting, video tutorials, discussion activities for students, and evaluation tools; 3) teachers are able to implement e-learning independently.